Intensified Olympic preparation: sleep and training-related hormonal and immune responses in water polo - Botonis, P. G.; Toubekis, A. G. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To investigate whether sleeping activity, hormonal responses, and wellness are altered in elite water polo players during their preparation toward the Tokyo Olympics.